Post-emergence application of glufosinate on maize hybrids containing the phosphinothricin acetyltransferase gene (pat) - Krenchinski, Fábio Henrique [UNESP]; Carbonari, Caio Antonio [UNESP]; de Castro, Edicarlos Batista [UNESP]; Rodrigues, Danilo Morilha [UNESP]; Cesco, Victor José Salomão [UNESP]; Costa, Renato Nunes [UNESP]; Velini, Edivaldo Domingues [UNESP] (Southern Cross Publishing, 2020)
Several maize hybrids that present the phosphinothricin acetyltransferase gene (pat) are available in the market. However, these hybrids have different resistance levels to glufosinate herbicides. The objective of the present work was to evaluate the resistance of maize hybrids containing the pat gene (as a selection marker) to glufosinate. Field experiments were conducted in two sites in the 2016/2017 crop season, using a randomized block design with a 2×7 factorial arrangement and four replications. The treatments consisted of two glufosinate rates (0 and 500 g ha-1) and seven maize hybrids, six containing the pat gene as a selection marker (Herculex®, Agrisure-TL®, Herculex Yieldgard®, Leptra®, Viptera-3®, and Power-Core®) and one without the pat gene (VT PRO®). Two field experiments were conducted in different sites. The analyzed variables were: ammonia accumulation, electron transport rate (ETR), percentage of injuries, 100-grain weight, and grain yield. The glufosinate-susceptible maize hybrid presented higher ammonia accumulations, lower ETR, and high percentage of injuries (100%), which caused total loss of grain production. Considering the evaluated glufosinate-resistant maize hybrids, Viptera-3 and Agrisure-TL presented the highest ammonia accumulations and percentages of injuries, and lower ETR than the other hybrids. The grain yield of glufosinate-resistant maize hybrids was not reduced due to the application of the 500 g ha-1 of glufosinate. Thus, glufosinate-resistant maize hybrids containing the pat gene are resistant to the application of 500 g ha-1 of glufosinate, and this practice can be recommended for maize crops.
Keywords: Ammonium accumulation; Electron transport rate; L-phosphinothricin; Pat gene; Zea mays L